Implemantasi Program Kampus Mengajar Guna Meningkatkan Literasi Dan Numerasi Di SDN Kenjeran 248 Surabaya - Grace Lordita Hatumena (Jurnal Pelayanan Hubungan Masyarakat, 2023)
Literacy and numeracy are fundamental competencies that have an important role in determining the quality of a nation. The problems that arise in the education sector have received great attention from the government. However, in fact, the literacy and numeracy competencies of students in Indonesia are still low and education has not developed as it should, so that it is far behind other countries. Therefore, the Ministry of Education, Culture, Research and Technology launched the Teaching Campus program as a form of solution to the problems experienced by schools affected by the pandemic. The Campus Teaching Program Batch 5 is held at SDN Kenjeran 248 Surabaya for sixteen weeks. The purpose of this activity is to improve students' literacy and numeracy skills, provide assistance with technology adaptation, and assist schools in administration. The implementation of the Teaching Campus program batch 5 at SDN Kenjeran 248 Surabaya provides many benefits for the school. Students' literacy and numeracy skills have increased. Students become more fluent in reading and are able to conclude the contents of a reading. In addition, students are able to memorize multiplication well.